A neuroimaging study of brain activity alterations in treatment-resistant depression after a dual target accelerated transcranial magnetic stimulation - Liu, Jiaoying; Shu, Yanping; Wu, Gang; Hu, Lingyan; Cui, Hailun (Frontiers in Psychiatry, 2024)
In this study, we designed a new transcranial magnetic stimulation (TMS) protocol using a dualtarget accelerated transcranial magnetic stimulation (aTMS) for patients with treatment resistant depression (TRD). There are fifty-eight TRD patients were recruited from the Second People's Hospital of Guizhou Province, who were respectively received dual-target (real continuous theta burst stimulation (cTBS) at right orbitofrontal cortex (OFC) and real repetitive transcranial magnetic stimulation (rTMS) at left dorsolateral prefrontal cortex (DLPFC)), single-target (sham cTBS at right OFC and real rTMS at left DLPFC), and sham stimulation (sham cTBS at right OFC and sham rTMS at left DLPFC). Resting-state functional magnetic resonance imaging (rs-fMRI) was acquired before and after aTMS treatment to compare characteristics of brain activities by use of amplitude of lowfrequency fluctuations (ALFF), fractional low-frequency fluctuations (fALFF) and functional connectivity (FC). At the same time, Hamilton Depression Scale-24 (HAMD24) were conducted to assess the effect. HAMD24 scores reduced significantly in dual group comparing to the single and sham group. Dual-target stimulation decreased not only the ALFF values of right fusiform gyrus (FG) and fALFF values of the left superior temporal gyrus (STG), but also the FC between the right FG and the bilateral middle frontal gyrus (MFG), left triangular part of inferior frontal gyrus (IFG). Higher fALFF value in left STG at baseline may predict better reaction for bilateral arTMS. Dualtarge stimulation can significantly change resting-state brain activities and help to improve depressive symptoms.This is a methods article with the length of 3937 for the main body of the text, footnotes, and all citations. And there are 4figures and 2tables included in this manuscript.